A comparative numerical study to compute ocular injury in boxing - Razaghi, R.; Biglari, H. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
Sport is responsible for between 25% and 40% of all eye injuries. Trauma is integrated to the nature of the sport, especially boxing, which is considered a high-risk sport for ocular injuries. Boxing not only brings about injury to the external side of the eye, but in nearly one third of cases, the intraocular components of the eye are also damaged, followed by serious visual acuity complications. However, so far there is a paucity of knowledge on the ocular injury as a result of a strong hook to the face during boxing. This study was, therefore, aimed to perform a dynamic finite element simulation to calculate the stresses and deformations to the components of the eye (i.e. the cornea, aqueous body, iris, ciliary body, vitreous body, sclera, retina, and optic nerve) as a consequence of a hook to the zygomatic and frontal skull bones of a boxer. To do that, well-verified finite element models of the human skull, eye, and punch developed by the current authors were employed to simulate the traumatic model of the skull. The resulting von Mises stresses and deformations in each component of the eye were calculated and compared. The results revealed higher stresses in the components of the eye as a result of a frontal impact compared to that of the zygomatic one. The concentration of the von Mises stresses in the eye components was mostly located in the lateral circumference of the globe. Regardless of the impact sites, the muscle experienced severe damage while the cornea, as the most anterior, and optic nerve, as the most posterior components of the eye, stayed safe with trivial amounts of stress and deformation. These results have implications not only for understanding the possible ocular injuries from a hook but also for providing comprehensive information to medical experts regarding the types of ocular injuries which may occur during boxing.